Molecular detection of Dientamoeba fragilis among patients at Raparin Teaching Hospital for Children in Erbil City, Iraq using nested PCR - Al-Qassab, Sarwat Ekram (Journal of Neonatal Surgery, 2025)
Dientamoeba fragilis is a globally distributed protozoan parasite that is recognized as a causative agent of gastrointestinal symptoms, particularly within pediatric populations. The incidence of infections has increased in recent years, largely due to the implementation of more sensitive molecular techniques that have enhanced both the detection and diagnosis of this organism. This study aimed to determine the prevalence of Dientamoeba fragilis among pediatric patients using nested PCR technique. It represents the first molecular investigation of this parasite in Iraq. A total of 100 stool specimens were collected from children aged between (>1 - 12) years. The analysis revealed higher prevalence rate of 19% using nested PCR compared to 17% observed through primary PCR. The highest infection rate was recorded in the age group of 1 to 3 years. These findings underscore the critical need of enhancing public and clinical awareness regarding D. fragilis infections within this country